La lectura crítica en el desarrollo del pensamiento en niños de sexto grado de Educación Básica de la escuela General Pintag en el año 2020 - 2021 - Monge Tigse, Pedro Enrique (2021)
This research work was developed in the "General Pintag" Educational Unit located in the parish of San Miguel of the Salcedo community of Cumbijín, with the purpose of answering the following Scientific problem How does critical reading influence the teaching-learning process in the development of thought? For which the general objective was proposed: Strengthen the teaching-learning process through critical reading for the development of thought; In the research modality, the quantitative approach called the positivist paradigm was used, through the use of the deductive method, that is, starting from the theory that exists until reaching the proposal. Work was done using a census of both educational authorities and parents. In each of the chapters of the degree works they correspond to each of the objectives achieved, one of them being the elaboration of eleven methodological strategies of critical reading developed through three levels that starts from the literal level, passes through the inferential level until reaching to the third level that is the evaluative critic. For the literal and inferential level, four strategies were designed respectively and for the critical evaluative level three strategies that are aimed at strengthening the development of children's thinking. After applying the methodological proposal, it was concluded that critical thinking is developed through activities of creative and analytical strategies developing the right hemisphere of the children under investigation.